KAJIAN PENGEMBANGAN ORGANISASI AKADEMI MARITIM INDONESIA (AMI) BITUNG - Sasto, La Bata (HOLISTIK, Journal Of Social and Culture, 2013)
Indonesia Maritime Academy in Bitung makes up an institution of private academy which organizes maritime profesional education in Bitung city. This institute was founded on april 10, 1988 and is registend on the base of the decree of the minister of education and culture number D 109/D/1990 date 21 February 1990, under the protection of the manguni foundation of Bitung. In its development the AMI of Bitung refers to the International Maritime Organization (IMO) regulational, STCW 1995 concerving Quality Standard System. By the enforvemen of the said regulation, the AMI of Bitung has not yet been able to carry out the whole learming-teaching process as requived by the quality standard system either viewed from the quality standard system either riwed from the aspect of learning aids or the aspeet of organization. This research is aimed to study the effecting factors which make up strength, weakness or oppotuonity and threaten faced by the organization. From the result of research it is suggested that the foundation and management of the AMI of Bitung can complete the learning aids and the organization structure in accordance with the Quality Standar System. Keywords : organization, maritim, management